At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
[tex]f(x)=\sqrt{x^2-1},g(x)=\sqrt{x-1}[/tex]
Hence [tex]f(x)/g(x)=\sqrt{\frac{x^2-1}{x-1}}=\sqrt{\frac{(x+1)(x-1)}{x-1}}=\sqrt{x+1}[/tex]
Hence [tex]f(x)/g(x)=\sqrt{\frac{x^2-1}{x-1}}=\sqrt{\frac{(x+1)(x-1)}{x-1}}=\sqrt{x+1}[/tex]
[tex]f(x) = \sqrt{x^{2} - 1} [/tex]
[tex]g(x) = \sqrt{x - 1} [/tex]
[tex]\frac{f(x)}{g(x)} = \sqrt{\frac{x^{2} - 1}{x - 1}} [/tex]
[tex]\frac{f(x)}{g(x)} = \frac{\sqrt{x^{2} - 1}}{\sqrt{x - 1}} [/tex]
[tex]\frac{f(x)}{g(x)} = \frac{\sqrt{x^{2} + x - x - 1}}{\sqrt{x - 1}} [/tex]
[tex]\frac{f(x)}{g(x)} = \frac{\sqrt{(x - 1)(x + 1)}}{\sqrt{x - 1}} [/tex]
[tex] \frac{f(x)}{g(x)} = \sqrt{x + 1} [/tex]
[tex]g(x) = \sqrt{x - 1} [/tex]
[tex]\frac{f(x)}{g(x)} = \sqrt{\frac{x^{2} - 1}{x - 1}} [/tex]
[tex]\frac{f(x)}{g(x)} = \frac{\sqrt{x^{2} - 1}}{\sqrt{x - 1}} [/tex]
[tex]\frac{f(x)}{g(x)} = \frac{\sqrt{x^{2} + x - x - 1}}{\sqrt{x - 1}} [/tex]
[tex]\frac{f(x)}{g(x)} = \frac{\sqrt{(x - 1)(x + 1)}}{\sqrt{x - 1}} [/tex]
[tex] \frac{f(x)}{g(x)} = \sqrt{x + 1} [/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.